Cost of Illness Study in Thyroid Patients: A Systematic Review - Seisye Junita Miru; Libriansyah; Mufarrihah; Yunita Nita (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: The thyroid has a vital role in growth, neurodevelopment, reproduction, and metabolism. About 300 million people around the world had been reported to be suffering from thyroid disorders, but more than half were unaware. The factors of sex, age, weight of disease, and other accompanying conditions should be considered, otherwise, it will cause a long time treatment period in which the cost will become higher from year to year. Purpose: The systematic review aims to provide an overview of the financial burden caused by thyroid disease for the communities, governments and health care providers. Method: A systematic review of publications in several databases, namely PUBMED, SCIENCE DIRECT, DOAJ, SCOPUS and GOOGLE SCHOLAR. Results: Six research articles were obtained from publications selected for systematic review. The reviewed articles show overviews of the cost of thyroid disease in several countries. The financial burden of thyroid patients in some countries varies, with different perspectives. The lowest to highest cost ranges from 0.125 USD/patient – 8106 USD/patient. Conclusion: The study in this review illustrates the various costs in different countries; the cost of screening, and thyroid surgery has the largest contribution compared to other costs; research on the financial burden suffered by thyroid patients in the future must be carried out continuously and periodically to be able to estimate the cost of therapy more appropriately to provide a useful data for health care providers, governments and the community. Direct medical costs are the largest proportion.